(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
The formation of innovative ideas is often associated with the problem of finding sources of financing. In accordance with this, the article emphasizes the importance and significance of leasing as an effective means of financing innovative activities. The factors of formation and development of innovative leasing in the leasing market are also given.The goal of the article is to improve the financial condition of the subjects, participants of the innovative leasing agreement, by evaluating their effectiveness, as well as accelerating the production of innovative products. To achieve this goal, the differences between innovative and classic financial leasing, the importance of the financial model of an innovative leasing agreement, the formulas that can be used to identify it, and a general overview of the innovative leasing mechanism are shown. The efficiency of using innovative leasing mechanisms at the state level and the level of business entities is presented. Scientific and practical proposals for the formation and further development of innovative leasing in the national financial market have been developed.